NUBDZATUL BAYAN SEBAGAI BASIC LEARNING DALAM MEMAHAMI KITAB KUNING DI PESANTREN - Dewi Sinta; Fathor Rozi; Syaifur Rizal (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Understanding the yellow book in pesantren tends to be very difficult and tedious. This is due to the complexity of mastering nahwu and sharraf and the methods used in pesantren are still classical methods. This prompted this research to analyze the Nubdhatul Bayan method as Basic Learning in understanding the yellow book in Islamic boarding schools. This research uses a qualitative approach with the type of case study research in Islamic boarding schools, especially in Ma'had Aly Nurul Jadid through data collection based on in-depth studies on observations, interviews and documentation, while the analysis technique used is data analysis techniques with the air flow model proposed by Miles & Huberman. The results of this study indicate that the application of the Nubdatul Bayan method as basic learning in understanding the yellow book in the tamhid ma'had aly Nurul Jadid class is very effective in facilitating prospective students in mastering the yellow book. The implications of this study make it possible to facilitate and accelerate a prospective mahasantri ma'had aly Nurul Jadid in understanding the yellow book.